Increased oxidative/nitrosative stress markers measured non- invasively in patients with high 2,3,7,8-tetrachloro-dibenzo-p-dioxin plasma level - Pelclová, Daniela; Navrátil, Tomas; Fenclová, Zdeňka; Vlčková, Štěpánka; Kupka, Karel; Urban, Pavel; Ridzon, Petr; Zikan, Vit; Landová, Ludmila; Syslová, Kamila; Kuzma, Marek; Kačer, Petr (Neuro-endocrinology letters, 2011)
OBJECTIVES: 2,3,7,8-tetrachloro-dibenzo-p-dioxin (TCDD) is a highly toxic persistent environmental contaminant, classified as a human carcinogen affecting any target organ. The mechanism of carcinogenesis by TCDD is unclear as TCDD shows a lack of direct genotoxicity. Experimental studies also support the role of oxidative stress in TCDD neurotoxicity and vascular dysfunction. The aim was to investigate markers of oxidative/nitrosative stress and inflammation using non-invasive methods in subjects who got ill due to severe occupational exposure to TCDD in the years 1965-1968. METHODS: In 11 TCDD-exposed patients, and 16 controls, the analysis of following oxidative products of lipids, proteins and nucleic acids in plasma, urine and exhaled breath condensate (EBC) was performed: 8-iso-prostaglandin F2α (8-isoprostane), 4-hydroxy-trans-2-nonenale (HNE), malondialdehyde (MDA), o-tyrosine (o-Tyr), 8-hydroxyguanosine (8-OHG), 8-hydroxy-2 ́-deoxy-guanosine (8-OHdG), 5-hydroxymethyluracil (5-OHMeU). In addition, nitric-oxide-tyrosine (NO-Tyr) and leukotriene (LT) B4, C4, D4, and E4 were detected by liquid chromatography-mass spectrometry/mass spectrometry (LC-ESI-MS/MS). TCDD was measured by HRGC/HRMS, body lipid content by densitometry. Single-photon emission spectrometry (SPECT) of the brain was performed and compared with the findings of the patients in 2008. RESULTS: Mean TCDD plasma level in 2010 was 175 ± 162 pg/g lipids (population level about 2 pg/g), total TCDD content in the body 5.16 ± 4.62 mg. Reduction of cerebral blood flow in SPECT progressed in 8 patients, finding was stable in 2 subjects, and improvement occurred in 1 patient. In the EBC, 10 from 12 markers (all except LT D4 and LT E4), were significantly increased in the patients (p<0.05). In the urine, 7 markers were significantly higher than in the controls (p<0.05): 8-isoprostane, MDA, HNE, LT C4, LT E4, o-Tyr and NO-Tyr. In plasma, only NO-Tyr and 8-OHG were elevated (p<0.05). CONCLUSION: NO-Tyr was increased in all matrices in dioxin-exposed patients. EBC is not limited to lung disorders as the markers of oxidative stress and inflammation were elevated in EBC of patients with normal lung functions. TCDD-induced oxidative stress and inflammation markers can be detected non-invasively in the EBC and urine in the follow-up of the highly-exposed patients. Their prognostic value, however, needs to be elucidated.
Keywords: Occupational Exposure; biologické markery; Oxidative Stress; Aged; analýza moči; reaktivní formy dusíku; lidé středního věku; reaktivní formy kyslíku; senioři; Polychlorinated Dibenzodioxins; Blood Chemical Analysis; Chemical Industry; Urinalysis; lidé; Middle Aged; polychlorované dibenzodioxiny; chemický průmysl; studie případů a kontrol; Up-Regulation; Female; upregulace; Biomarkers; Male; ženské pohlaví; Case-Control Studies; osmolární koncentrace; Humans; oxidační stres; mužské pohlaví; Herbicides; herbicidy; pracovní expozice; Osmolar Concentration; Reactive Oxygen Species; biochemická analýza krve; Reactive Nitrogen Species